Waterschappen (Irrigation Agencies) in Vorstenlanden Surakarta and Yogyakarta, 1900-1942 - Machmoed Effendhie; Arif Rahman Bramantya (Humaniora, 2017)
The purpose of this study is to track the introduction of the irrigation agency (Watershappen) in the Vorstenlanden area Surakarta and Yogyakarta as well as effects on the relationship between farmers, farmers and plantation owners. In addition, this study aims to understand the patterns of institutional change and the water distribution system in the Vorstenlanden region and consequently on agriculture and plantation. State involvement in the problem of water distribution in the Vorstenlanden area causing a collision between a proportional system that has been done by the traditional farmers with absolute system applied state. As a result, irrigation conflicts arise between plantation because of the use of a watershed point for some plantations. Conflicts between plantations and farmers because of water scarcity due to the autonomy of the estate in the distribution of water to agricultural land and conflicts between farmers as water encroachment without the knowledge of other farmers.